Emotional scene remembering: A combination of disturbing and facilitating effects of emotion? - Bouvarel, David; Gardette, Jeremy; Saint-Macary, Manon; Hot, Pascal (Frontiers in Behavioral Neuroscience, 2022)
An emotion-induced memory trade-off effect is frequently reported when participants have to memorize complex items that include both neutral and emotional features. This bias corresponds to better remembering of central emotional information accompanied by poor performance related to neutral background information. Although the trade-off effect has been mainly associated with attentional bias toward emotional content, findings suggest that other non-attentional cognitive processes could also be involved. The aim of this work was to assess whether emotional effects would be reported apart from their influence on attentional processing in an immediate delay memory task. Three studies were conducted. In Study 1, manipulation of the diffusion quality of emotional content allowed us to select focal emotional pictures versus diffuse emotional pictures, which prevented attentional focus. The two studies that followed consisted of a recognition task of low- and high-complexity pictures in which we used partial visual cues during the test that could display either the emotional elements (i.e., central patch cues, Study 2) or the peripheral elements (i.e., peripheral patch cues, Study 3) of the focal emotional pictures. Results from Studies 2 and 3 replicated traditional trade-off effects only for high-complexity pictures. In addition, diffuse emotional pictures were associated with lower memory performance than were neutral pictures, suggesting that emotion features could both disturb and enhance (via their attentional effect) encoding processes.